2011
DOI: 10.5194/acp-11-3631-2011
|View full text |Cite
|
Sign up to set email alerts
|

Episodes of cross-polar transport in the Arctic troposphere during July 2008 as seen from models, satellite, and aircraft observations

Abstract: Abstract. During the POLARCAT summer campaign in 2008, two episodes (2-5 July and 7-10 July 2008) occurred where low-pressure systems traveled from Siberia across the Arctic Ocean towards the North Pole. The two cyclones had extensive smoke plumes from Siberian forest fires and anthropogenic sources in East Asia embedded in their associated air masses, creating an excellent opportunity to use satellite and aircraft observations to validate the performance of atmospheric transport models in the Arctic, which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 56 publications
(69 reference statements)
3
41
0
Order By: Relevance
“…Studies that have used FLEXPART CO concentration fields (χ CO ) have found satisfactory agreement between model output and measurements (Stohl, 2006;Paris et al, 2009;Hirdman et al, 2010;Sodemann et al, 2011;Stohl et al, 2013Stohl et al, , 2015Eckhardt et al, 2015). In the Alaskan Arctic for the day of 18 April 2008, Warneke et al (2009) described a slope of 0.9 for a linear fit between FLEXPART model output of χ CO and airborne measurements of CO with a least-squares correlation coefficient of 0.63.…”
Section: Anthropogenic Pollution Tracer Fieldsmentioning
confidence: 98%
“…Studies that have used FLEXPART CO concentration fields (χ CO ) have found satisfactory agreement between model output and measurements (Stohl, 2006;Paris et al, 2009;Hirdman et al, 2010;Sodemann et al, 2011;Stohl et al, 2013Stohl et al, , 2015Eckhardt et al, 2015). In the Alaskan Arctic for the day of 18 April 2008, Warneke et al (2009) described a slope of 0.9 for a linear fit between FLEXPART model output of χ CO and airborne measurements of CO with a least-squares correlation coefficient of 0.63.…”
Section: Anthropogenic Pollution Tracer Fieldsmentioning
confidence: 98%
“…CO columns are now assimilated operationally at ECMWF in the Global Monitoring for Environment and Security (GMES)/Monitoring Atmospheric Composition and Climate (MACC) forecasting model to produce a chemical forecast of CO fields, and are also used in a variational Bayesian system to infer the global distribution of CO emissions (Fortems-Cheiney et al 2009). They have also served as reference for the Polar Study using Aircraft, Remote Sensing, Surface Measurements and Models, of Climate, Chemistry, Aerosols, and Transport (POLARCAT) International Polar Year (IPY) activities to plan aircraft campaigns and to study the transport of pollution plumes from boreal fires moving toward the Arctic (Pommier et al 2010;Sodemann et al 2011).…”
Section: Impact Of Ias I On Atmos Ph E Ric Composition Studiesmentioning
confidence: 99%
“…Fractional cloudiness derived from CALIPSO data revealed shortcomings in simulated cloudiness by a climate model in a more pronounced fashion than evaluations based on passive observations [9]. CALIPSO lidar curtains and in situ aircraft measurements were analyzed to assess the model performance during the POLARCAT field campaign [11]. CALIOP data were used to evaluate Weather Research and Forcasting model [13] inline with chemistry (WRF/Chem) [14] simulated wildfire-plume heights over Asia [12].…”
Section: Introductionmentioning
confidence: 99%